The Influence Of Marketing Mix Strategies On Consumer Buying Behavior: Malaysian Perspective - Wei, Seow Heng (2009)
The purpose of this paper is to examine the influence of marketing mix strategies (MMS) on Malaysian consumers' buying behavior. The traditional marketing mix strategies are defined by the 4Ps of marketing, namely product, price, promotion and place.